Analisis Usaha Penggemukan Sapi Madras Di Serdang Bedagai - Tasyaul Azkia; Raudhatul Jannah; Anita Salsabila; Melyana Melyana; Kiagus Muhammad Zain Basriwijaya (Botani : Publikasi Ilmu Tanaman dan Agribisnis, 2025)
Cattle farming is crucial to the economy, particularly in agricultural countries, providing meat, milk, and leather, as well as raw materials for related industries. In Indonesia, cattle farming is growing rapidly, with Perbaungan, Serdang Bedagai Regency, North Sumatra, showing significant development due to favorable conditions such as fertile land and abundant feed resources. This study evaluates the fattening of Madras cattle through field experiments, using a balanced mix of concentrate and grass. The results suggest that fattening cattle is a viable business, contributing to national beef production and food security. The total monthly production cost for 70 cattle is Rp 59,283,000, indicating economic feasibility for further development.